Akhlak Siswa terhadap Guru Pada Pendekatan Normatif di Dalam Al-Qur’an dan Hadis - Khoirunisa, Khoirunisa; Sutrisno, Sutrisno (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The normative approach is to understand religion using the framework of God's knowledge, the view of the main and original teachings from God in which there is no human reasoning. The purpose of this study was to see the morals of students towards teachers according to the Qur'an and Hadith. This research method is descriptive qualitative. The method in this study is a library method, the data collected are books and previous studies that are relevant for this research. In the data source section, there are verses from the Qur'an and hadith that contain students' morals towards teachers, reading books that refer to research theory, and several related previous studies. Data collection techniques used reading and note-taking techniques. The data analysis technique in this study is content analysis using a normative approach to the text in the verses of the Qur'an and Hadith and in the form of articles from the journal Sinta 2-5 as many as 4 articles containing moral habits based on a normative approach. Normative matters regarding student morals in the school community and family environment do need to be emphasized according to the verses of the Qur'an and hadith, this is able to form noble character in children from an early age.